Integrated Business Mentoring: Efforts to Improve Sustainable Business, in Mlokorejo Village, Jember, Indonesia - Yani Dahliani; Hary Sulaksono (TGO Journal of Community Development, 2024)
The small business mentoring program in Mlokorejo village, Jember aims to increase the capacity and competitiveness of small businesses so that they can grow sustainably and contribute to local economic development. The program aims to provide managerial and technical skills training, introduction of new technologies, and market access support. The program is carried out through three main stages: planning, implementation, and evaluation. In the planning stage, the specific needs of small businesses are identified through surveys and discussions with stakeholders. The implementation stage includes training, mentoring, and market access support. Evaluation was carried out using qualitative analysis methods through interviews, focus group discussions, and field observations. The results showed significant improvements in the managerial and technical skills of participants, adoption of new technologies that increase production efficiency, and wider market access that contributed to increased sales. However, challenges remain in terms of access to financing and product development that require further attention. The program has succeeded in increasing the capacity of small businesses through the training and support provided. Adoption of new technologies and expanded market access have had a positive impact on productivity and sales.